1997
DOI: 10.2208/prohe.41.481
|View full text |Cite
|
Sign up to set email alerts
|

Study on generation of wind-dirven current and behavior of the density interface between salt and fresh waters in Lake Abashiri

Abstract: In recent years, Lake Abashiri has been confronted with serious problems due to water accidents induced by aoshio and eutrophication. By using a fish detector and ADCP, we could make clear the spatial and temporal structure of density stratified flow, the short-term behaviors of salinocline(halocline) just after the occurrence of aoshio, and the overall characteristics of the flow in this lake. Based on the results of the observation, we carried out the numerical analysis regarding to the time-varying behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This means that seawater moving upslope mixes with the upper fresh water in the lower Abashiri River. Ikenaga et al (1997) revealed by ®eld observation and numerical simulation that vertically constant salinity in the Abashiri River channel results from the breakage of a salt wedge by tidal currents. Figure 5 shows hourly records of wind vectors at sites W1 and W2 for the period of 5 June±23 August.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This means that seawater moving upslope mixes with the upper fresh water in the lower Abashiri River. Ikenaga et al (1997) revealed by ®eld observation and numerical simulation that vertically constant salinity in the Abashiri River channel results from the breakage of a salt wedge by tidal currents. Figure 5 shows hourly records of wind vectors at sites W1 and W2 for the period of 5 June±23 August.…”
Section: Methodsmentioning
confidence: 99%
“…Winds at site W1 were then very weak over these periods. This suggests that the northward wind induced entrainment and consequent uplift of the lower cold saline water o Memanbetsu Bay by southward countercurrents in the bottom layer ( Figure 6; Ikenaga et al, 1997). Figure 10 shows time series of¯ow velocity and water temperature in the lower layer of site MD.…”
Section: Seawater Intrusionmentioning
confidence: 97%
See 3 more Smart Citations